Reaction Time in Stutterers - NP, Nataraja; CS, Venkatesh; A, Jagadish (Journal of All India Institute of Speech and Hearing)
In many studies reaction time has been found to be delayed in stutterers. Many of these studies have used auditory stimuli to obtain reaction time. The present study was carried out to find the possible differences in reaction time for auditory and visual stimuli. The reaction time to auditory and visual stimuli in 10 stutterers and 10 normals were obtained. It was found that the reaction time was delayed in stutterers under both the conditions, when compared with normals. Further, it was also found that the stutterers were slower in responding to visual stimuli than to auditory stimuli.